Soluble adhesion molecules in muscular dystrophy - Saito, Toshio; Yamamoto, Yuko; Shinno, Susumu (No to hattatsu, 2002)
To determine whether soluble adhesion molecules are affected in muscular dystrophy, we measured serum levels of creatine kinase (CK), soluble vascular cell adhesion molecule-1 (sVCAM-1), soluble intercellular adhesion molecule-1 (sICAM-1), soluble (s) E-selectin, and fibrin and fibrinogen degradation products (FDP) in 25 patients with Duchenne muscular dystrophy (DMD), 7 with Becker muscular dystrophy, 7 with Fukuyama type congenital muscular dystrophy, 6 with myotonic dystrophy (MyD), and 5 with spinal muscular atrophy (SMA) type 2, and also serum sVCAM-1, sICAM-1, and sE-selectin in 9 healthy controls. The levels of sVCAM-1 in the patients with DMD were 367.0-852.0 ng/ml (552.8 +/- 23.1) and significantly elevated than those in the patients with MyD, SMA type 2, and controls. The levels of sICAM-1 and sE-selectin in the patients with muscular dystrophy were 0.2-376.0 ng/ml and 17.9-119.0 ng/ml, respectively. They were also elevated than those in the patients with SMA type 2 and controls, but not significantly. The levels of sVCAM-1 and sE-selectin in the patients with DMD significantly correlated with age. There was no correlation between the levels of soluble adhesion molecules and those of CK or FDP in any groups. These changes of soluble adhesion molecules may reflect the process of muscle destruction and endothelial cell activation in muscular dystrophy.